(3GdGKQ GdGbJUGOi ddSjGSGJ GdSYQjI Ydi eMUhd GdYOS aj eUQs - (3aQ L, QTG eMeO CMeO s (2022)
(3JYQV GdbWGY GdRQGYi aj GdBhfI GdCNQjI dcKjQj ef GdCReGJ hGdEVWQGHGJ GdeJJGdjI GdPi LYdJ GdOhdI JSYi fMh RjGOI GdeSGMGJ GdefRQYI HCge GdeMGUjd GdGSJQGJjLjI HGdCQGVj GdLOjOI dRjGOI GdEfJGL hGdMO ef GdGSJjQGO hYOe GdCYJeGO Ydi GdNGQL aj JhajQ GdZPGA, hJYJHQ GdHbhdjGJ ef Cge GdeMGUjd GdJi JSYi GdOhdI dJMbjb eYOdGJ eQJaYI ef GdCef GdZPGFi dgG,s
(3jMJhj Ydj eQGLY s
(3edNU HGddZI GdGfLdjRjIs
Keywords: (3GdYOSs -- (3RQGYIs; (3GdYOSs -- (3GbJUGOjGJs